Design of Extracurricular Project for Strengthening the Profile of Pancasila Students and Rahmatan Lil Alamin Students in Madrasah Ibtidaiyah - Nurmayuli, Nurmayuli; Lailatussadah, Lailatussaadah; Hayati, Salma; Hayati, Cut Intan (Dirasah: Jurnal Pendidikan Islam, 2025)
The role of extracurricular learning is crucial in supporting intra-curricular and co-curricular learning in Madrasah Ibtidaiyah (MI). However, many teachers still face difficulties in determining activities for the Strengthening the Profile of Pancasila Students and Rahmatan Lil Alamin Students (P5PPRA) project within extracurricular learning. This study aims to design an extracurricular P5PPRA framework for MI. The research method used is the Design-Based Research (DBR) model. The study was conducted at MI in Lhokseumawe City, involving all MI school stakeholders, including the Head of Madrasah and teachers. The results indicate that the P5PPRA extracurricular design for MI can be structured around two themes: sustainable living and engineering to build the Republic of Indonesia. Each project theme is implemented through three phases: Phase A (introduction), Phase B(design), and Phase C (implementation). This design is expected to assist teachers in developing innovative extracurricular learning that aligns with the needs of the madrasah and students